‘THE MENTAL AND REPRODUCTIVE HEALTH OF ADOLESCENT GIRLS WITH SPECIAL REFERENCE TO THE INDIGENOUS TIWAS OF INDIA’ (Proceedings of the World Conference on Women’s Studies, 2023)
Adolescence is a critical period in everyone’s life, but it becomes particularly significant for an adolescent girl reaching childbearing age. The following research investigates the issues concerned in enhancing the reproductive and mental health education of adolescent girls of the Tiwas of West Karbi Anglong district in Assam, India. According to UNICEF data (n.d.), India comprises one-third of the world’s child bride population. However, unlike the tribes of Odisha, India (Pradhan, 2022) where child marriages are prevalent, there is no forced child marriage among the tribes of Assam. In contrast, the choice of marriage is usually made by the Tiwa adolescent girl herself. Early pregnancy in developed countries such as the United States and the United Kingdom is equally alarming. An adolescent girl who reaches puberty undergoes the same physical changes, fear, anxiety, and excitement when entering adulthood irrespective of their socioeconomic status. There is currently a lack of research into the reproductive and mental health of Tiwa adolescent girls in Assam. Therefore, this paper investigates the issues of reproductive and mental health faced by adolescent girls in the Tiwa community by collectingprimary data from the field. The best practices of developed nations will be studied from secondary data, to educate Tiwa adolescents about individual rights, marriage age, domestic violence and the dangers of early pregnancy. Finally, the findings will provide a counter-narrative to the common notion that child marriage is enforced in India; instead, it is chosen by the adolescent herself in many tribes of Northeast India.Keywords:  adolescent health, child marriage and pregnancy
Keywords: Child marriage; Teen pregnancy; Adolescent physical health; Adolescent mental health; Tribal marriage custom